2020
DOI: 10.1101/2020.09.01.278226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid adaptation to malaria facilitated by admixture in the human population of Cabo Verde

Abstract: Humans have undergone large migrations over the past hundreds to thousands of years, exposing ourselves to new environments and selective pressures. Yet, evidence of ongoing or recent selection in humans is difficult to detect. Many of these migrations also resulted in gene flow between previously separated populations. These recently admixed populations provide unique opportunities to study rapid evolution in humans. Developing methods based on distributions of local ancestry, we demonstrate that this sort of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…We then called local ancestry with RFMix v1.5.4 ( Maples et al 2013 ) PopPhased under a 2-way admixture model using the West African and European reference genotypes described above. These local ancestry calls are publicly available via Zenodo ( Hamid et al 2020 ). Ancestry proportions estimated with ADMIXTURE and RFMix here are highly correlated with results from Beleza et al (2013) , using the same genotype data but with different software [ frappe ( Tang et al 2005 ) and SABER ( Tang et al 2006 )] and an older reference dataset ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We then called local ancestry with RFMix v1.5.4 ( Maples et al 2013 ) PopPhased under a 2-way admixture model using the West African and European reference genotypes described above. These local ancestry calls are publicly available via Zenodo ( Hamid et al 2020 ). Ancestry proportions estimated with ADMIXTURE and RFMix here are highly correlated with results from Beleza et al (2013) , using the same genotype data but with different software [ frappe ( Tang et al 2005 ) and SABER ( Tang et al 2006 )] and an older reference dataset ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Duffy-null allele at the DARC locus is protective against malaria-causing Plasmodium vivax infection, which is estimated to be one of the strongest selective pressures in recent human history. The Duffy-null allele is nearly fixed in sub-Saharan African populations and mostly absent in non-African populations, producing a classic signal in which the DARC locus is an outlier in its proportion of local African ancestry in multiple admixed populations [21][22][23][24][25]. However, the strength of selection at the DARC locus is not typical of human adaptation.…”
Section: Phenotypically Important Loci and Regions Under Selectionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pgen.1009374.g001 or adaptive [18][19][20][21][22][23][24][25][26] alleles. In this context, we use ancestry to describe "genetic ancestry"-the population origins of material within a genome.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies have also demonstrated that admixture between modern human populations following a period of isolation can result in the adaptive introgression of previously population‐specific advantageous alleles. This phenomenon has occurred repeatedly in recent human history, for example for alleles associated with malaria resistance, 54–58 skin depigmentation, 59 and lactase persistence 9 …”
Section: Genome‐wide “Scans” For Signatures Of Positive Selection In mentioning
confidence: 99%